Pengaruh Sharia Compliance dan Islamic Corporate Governance Terhadap Kinerja Keungan Bank BPRS Paduarta Sinsani Medan - Abul Khoidir Nasution; Syahrul Amsari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study explores the influence of Sharia Compliance and Islamic Corporate Governance on the financial performance of Bank BPRS Paduarta Insani Medan. Using an associative approach and employing purposive sampling techniques, the research utilizes primary data analyzed with SPSS 25 software. The results of the normality test indicate that the research data is normally distributed. The multicollinearity test shows no symptoms of multicollinearity among independent variables. The results of the partial regression test (t-test) demonstrate that both Sharia Compliance and Islamic Corporate Governance have a positive and significant impact on the financial performance of Bank BPRS Paduarta Insani Medan. The coefficient of determination (R2) is 0.961, signifying that the independent variables can explain 96.1% of the variation in the bank's financial performance, while the remaining percentage is influenced by other variables outside the regression model. In conclusion, Sharia Compliance and Islamic Corporate Governance have a positive and significant influence on the financial performance of Bank BPRS Paduarta Insani Medan. These findings are consistent with previous research that supports the importance of Sharia compliance and good corporate governance in the context of Islamic banking.